2018
DOI: 10.1371/journal.pone.0192434
|View full text |Cite
|
Sign up to set email alerts
|

Preconception paternal bisphenol A exposure induces sex-specific anxiety and depression behaviors in adult rats

Abstract: Bisphenol A (BPA), an environmental endocrine-disrupting compound, has drawn a great attention for its adverse effect on behavioral development. Maternal exposure to this compound has been reported to induce anxiety and depression in offspring, but the effect of its paternal exposure is rarely discussed. This study investigated whether preconception paternal BPA exposure can affect the emotions of male rats and their offspring. Eighteen adult male rats (F0) received either a vehicle or 50 μg/kg/day BPA diet fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Furthermore, numerous paternal chronic stress paradigms reshape physiological and behavioral stress vulnerability across generations (Dietz et al., ; Gapp et al., ; Rodgers et al., ; Short et al., ) and paternal cocaine exposure alters cocaine preference and hippocampal‐dependent memory in male offspring (Le et al., ; Vassoler et al., ; Wimmer et al., ). Other paternal conditions with cross‐generational effects in rodents include exposures to environmental toxicants such as bisphenol A (Fan et al., ) as well as exposures to beneficial conditions such as enriched housing (Yeshurun et al., ) or free access to a running wheel (Short et al., ). As rodent sires are not involved in offspring gestation or rearing in these studies, the contribution of the father to offspring development is likely restricted to the germline.…”
Section: Heritability Of the Preconception Environmentmentioning
confidence: 99%
“…Furthermore, numerous paternal chronic stress paradigms reshape physiological and behavioral stress vulnerability across generations (Dietz et al., ; Gapp et al., ; Rodgers et al., ; Short et al., ) and paternal cocaine exposure alters cocaine preference and hippocampal‐dependent memory in male offspring (Le et al., ; Vassoler et al., ; Wimmer et al., ). Other paternal conditions with cross‐generational effects in rodents include exposures to environmental toxicants such as bisphenol A (Fan et al., ) as well as exposures to beneficial conditions such as enriched housing (Yeshurun et al., ) or free access to a running wheel (Short et al., ). As rodent sires are not involved in offspring gestation or rearing in these studies, the contribution of the father to offspring development is likely restricted to the germline.…”
Section: Heritability Of the Preconception Environmentmentioning
confidence: 99%
“…Several recent epidemiological studies have demonstrated a correlation between urinary BPA levels and obesity (55,56). Moreover, as previously described, the exposure to BPA can induce adverse effects on neurological control, suggesting an involvement in behavior management (57)(58)(59). A very recent study performed on obese subjects demonstrated a reduction in most phthalate levels after a dietary intervention (60).…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, examination of effects of maternal exposure to epoxy resin on offspring has been focused (Golub et al, 2010). Indeed, numerous experiments using animal models have reported that gestational BPA exposure induces behavioral alteration: hyperactivity, anxiety-and depression-like behaviors (Braun et al, 2011;Cox et al, 2010;Fan et al, 2018;Komada et al, 2014;Luo et al, 2013;Nakamura et al, 2012). Causality of early BPA exposure and behavioral change has been supported by observations in humans (Braun et al, 2011;Braun et al, 2009;Evans et al, 2014;Perera et al, 2012).…”
Section: Discussionmentioning
confidence: 99%